Strategic Programs to Release the Vision of Agriculture 5.0 in North Sulawesi, Indonesia to get much Income - Tulungen, Franky Reintje (Budapest International Research and Critics University, 2022)
This study aims to formulate a vision of Agriculture 5.0 in North Sulawesi, and to create strategic programs to realize the vision of Agriculture 5.0 in North Sulawesi. This research is policy research to realize the vision of Agriculture 5.0 in North Sulawesi using the Competitive Intelligence (CI) method. The results of the study indicate that the existing facilities and infrastructure in North Sulawesi Province can support the Vision of Agriculture 5.0 in North Sulawesi. The vision of Agriculture 5.0 in North Sulawesi is the use of robotic systems to increase the efficiency of agricultural businesses and take advantage of this economic growth to improve the quality of human resources and natural resources by prioritizing sustainable development. The robotic system in question uses unmanned ground vehicles for agricultural land processing, nurseries, plant planting, and plant maintenance, and unmanned aerial vehicles for soil monitoring, plant maintenance, phenotype observation, and plant health mapping. Strategic programs to realize the vision of Agriculture 5.0 are establishing an agricultural information system, farmer organization, and farmer partnership with stakeholders.